Active Touch During Shrew Prey Capture - Munz, Martin; Brecht, Michael; Wolfe, Jason (Frontiers in Behavioral Neuroscience, 2010)
Although somatosensation in multiple whisker systems has been studied in considerable detail, relatively little information is available regarding whisker usage and movement patterns during natural behaviors. The Etruscan shrew, one of the smallest mammals, relies heavily on its whisker system to detect and kill its highly mobile insect prey. Here, we tracked whisker and body motion during prey capture. We found that shrews made periodic whisker movements (whisking) with frequencies ranging from 12 to 17 Hz. We compared shrew and rat whisking and found that shrew whisking was smaller amplitude and higher frequency than rat whisking, but that the shrew and rat whisking cycle were similar in that the velocity was higher during retraction than protraction. We were able to identify four phases during the shrew hunting behavior: (i) an immobile phase often preceding hunting, (ii) a search phase upon the initiation of hunting, (iii) a contact phase defined by whisker-to-cricket contact, and (iv) an attack phase, characterized by a rapid head movement directed towards the cricket. During the searching phase, whisking was generally rhythmic and whiskers were protracted forward. After prey contact, whisking amplitude decreased and became more variable. The final strike was associated with an abrupt head movement towards the prey with high head acceleration. Prey-capture proceeded extremely fast and we obtained evidence that shrews can initiate corrective maneuvers with a minimal latency < 30 ms. While the shrew’s rostrum is straight and elongated during most behaviors, we show for the first time that shrews bend their rostrum during the final strike and grip their prey with a parrot beak shaped snout.